The Influence of Intergenerational Training, Information Technology, and Generational Conflict Management on Employee Engagement in a Jakarta Consulting Services Company - Wuryanti, Lestari; Suhara, Ade; Mayasari, Nanny; Vandika, Arnes Yuli (West Science Interdisciplinary Studies, 2024)
The rapid expansion of the crypto asset market presents significant challenges related to market transparency, this study examines the influence of intergenerational training, information technology adoption, and generational conflict management on employee engagement in a consulting services company in Jakarta. Using a quantitative approach, data were collected from 250 employees via a structured questionnaire and analyzed with SPSS version 25. The results reveal that all three factors significantly contribute to employee engagement, with intergenerational training being the strongest predictor, followed by information technology adoption and generational conflict management. The study highlights the importance of fostering collaboration across generations, leveraging technology for efficient workflows, and addressing generational conflicts to enhance workplace engagement. These findings offer actionable insights for organizations managing diverse workforces in similar contexts.